Strategies to Improve Taxpayer Compliance through Regional-Based Supervision Activities at KPP Pratama Pasuruan - Arinda, Jeny; Hadiyati, Ernani; Muawanah, Umi (International Journal of Economics Development Research (IJEDR), 2025)
This study analyzes the implementation of region-based supervision at the Pratama Tax Service Office (KPP Pratama) Pasuruan with the objective of improving taxpayer compliance and revenue realization. Employing a qualitative research approach, data were collected through interviews with tax officials and taxpayers, open-ended questionnaires, observations, and document reviews. The analysis combined descriptive thematic methods with SWOT analysis to capture both internal and external factors influencing supervision effectiveness. Findings reveal that KPP Pratama Pasuruan demonstrates strong employee commitment, effective use of technology, and structured procedures, which contribute to its consistent revenue achievements. However, challenges remain, including limited human resources, weaknesses in IT integration, and insufficient supervision evaluations. The SWOT results position the office in Quadrant I (aggressive strategy), indicating that strengths and opportunities outweigh weaknesses and threats. Consequently, the study recommends growth-oriented strategies such as optimizing information technology integration (CRM, SIDJP, GIS), segmenting taxpayers by compliance risk, intensifying education and outreach programs, strengthening inter-agency collaboration, and enhancing internal supervisory capacity. These findings provide both practical insights for improving regional tax administration in Indonesia and theoretical contributions to the discourse on compliance management, digitalization, and administrative reform.